Elementer i Grundtvigs politiske tænkning - Damsholt, Tine (Grundtvig-studier, 1995)
Grundtvig’s Political Theories By Tine Damsholt Grundtvig’s positive view of the Danish absolute monarchy has often been a problematic issue in today’s understanding of Grundtvig’s political ideas. It is a common view that in 1848 Grundtvig turned a political somersault, suddenly becoming a democrat after being a fervent adherent of absolutism. Quite a few have wanted either to see a break in Grundtvig’s political view or tried to explain away his apparently »undemocratic« attitude. However, if one examines Grundtvig’s basic political opinions, it is possible to establish a continuity in his political view. It is possible to see his apparent change of attitude as an expression of inevitable consequences of his idea of what were the central democratic elements in relation to the changing political situations.The analysis of Grundtvig’s view of democracy and representative government must take its point of departure in the political tradition that Grundtvig had grown up in. The ideal concept of the 18th century of absolute monarchy as the interpreter of the people’s voice is an essential background for the understanding of Grundtvig’s praise of Danish absolute monarchy in the period before and after the Danish constitution came into effect.Grundtvig’s political ideal can be epitomized as a unity of the two concepts of the King’s hand and the people’s voice, i.e. an absolute King listening to the people’s voice as it finds expression in a free debate, in writing and in speech, in an enlightened people. The enlightenment of the people is crucial to Grundtvig, and the gist of his criticism of the French Revolution is that the unenlightened mob assumed power. The folk high school, where the people is enlightened and educated to rise above narrow selfish interests to look at the common good, is thus a central part of Grundtvig’s political universe.Grundtvig also maintained this ideal after the Danish absolute monarchy was abolished in 1848. He claimed that this was the original and therefore the true Danish constitution, thus embracing the national-romantic tradition.